Hemorrhages of the second half of pregnancy - Pérez Aliaga, Carlos (2015)
Bleeding occurring in the second half of pregnancy causes important maternal and infant morbidity and even mortality; at the Instituto Nacional Materno Perinatal it compromises between 9 and 15% of all gestations. We recall it is associated to premature delivery, abruption placenta, placenta previa, disseminated intravascular coagulation. Treatment frequently requires blood and blood derivates transfusions as well as performing surgical procedures, including emergency hysterectomy. This is a review of second half of pregnancy hemorrhage causes; we emphasize precocious diagnosis and timely treatment of these pathologies.